BAFFR expression in circulating T follicular helper (CD4+CXCR5+PD-1+) and T peripheral helper (CD4+CXCR5−PD-1+) cells in systemic lupus erythematosus - Sagrero-Fabela, Nefertari; Ortíz-Lazareno, Pablo C; Salazar-Camarena, Diana C; Cruz, Alvaro; Cerpa-Cruz, Sergio; Muñoz-Valle, José F; Marín-Rosales, Miguel; Alvarez-Gómez, Jhonatan A; Palafox-Sánchez, Claudia A (Lupus, 2023)
Background Circulating T follicular helper (cTfh) and T peripheral helper (Tph) subpopulations are shown to be higher in systemic lupus erythematosus (SLE) patients and have been involved in promoting extrafollicular B cell responses. However, a possible association with the B cell activating factor (BAFF), a cytokine mainly related to B cell responses and disease activity in SLE, has not been investigated. Therefore, this study aimed to evaluate the association of cTfh and Tph subpopulations with the BAFF system expression and clinical activity in SLE patients. Methods This study included 43 SLE patients and 12 healthy subjects (HS). The identification of cTfh (CD4+CXCR5+PD-1+), Tph (CD4+CXCR5−PD-1+) cells, expression of membrane-bound BAFF (mBAFF), BAFFR, TACI, BCMA, and intracellular IL-21 was performed by flow cytometry. Serum levels of IL-21, CXCL13, and BAFF were analyzed using ELISA. The SLEDAI-2K score was used to evaluate disease activity in SLE patients. Results Compared with HS, SLE patients showed a significantly increased percentage of cTfh and Tph cells, higher in patients with clearly active disease. SLE patients had markedly higher IL-21-producing cTfh and Tph cells than HS. Both subpopulations were positively correlated with the disease activity in SLE patients. Tph cells were negatively correlated with CD19+CXCR5+ B cells and positively correlated with CD19+CXCR5− B cells. A low expression of mBAFF and their receptors TACI and BCMA was found on cTfh and Tph cells in SLE patients and HS. However, SLE patients with clearly active disease showed decreased expression of BAFFR on cTfh and Tph subpopulations than patients with mildly active/nonactive disease. Serum IL-21, CXCL13, and BAFF levels were higher in SLE patients than in HS. Levels of CXCL13 were correlated with disease activity. Non-significant correlations were observed among T cell subpopulations and IL-21, CXCL13, and BAFF levels. Conclusions This study emphasizes the importance of cTfh and Tph cells in SLE pathogenesis. Besides the importance of IL-21, our results suggest that BAFFR could play a role in cTfh and Tph subpopulations in the autoimmunity context.